Clear transparent cellulose nanopaper prepared from a concentrated dispersion by high-humidity drying. Issue 4 (8th January 2018) - Isobe, Noriyuki; Kasuga, Takaki; Nogi, Masaya
Abstract : Optically transparent paper is fabricated from concentrated cellulose nanofiber dispersion by high-humidity drying. Abstract : Optically transparent cellulose nanopaper is a promising candidate for flexible device substrates because of its light weight, surface smoothness, and high dimensional stability with respect to temperature. Conventionally, clear transparent nanopaper has been fabricated from cellulose nanofiber dispersions with quite low concentration: less than 0.5 wt%. However, this diluteness leads to several problems, such as huge energy consumption and long operation time for drying. Therefore, nanopaper should be fabricated from a concentrated dispersion to mitigate these problems. In this study, transparent nanopaper was fabricated from cellulose nanofiber dispersions with various concentrations (0.24–1.81 wt%). Optical experiments revealed that the haze of the transparent nanopaper increased monotonically with cellulose nanofiber dispersion concentration, when the cellulose nanofiber dispersion was prepared from holocellulose pulp and conventional over-drying was applied. Based on our insight into the origin of this increase in the haze of transparent nanopaper, we developed high-humidity drying, which successfully produced clear transparent nanopaper from a concentrated dispersion without prolonged drying time.